In vitro antioxidant and anti-arthritic activity of certain dihydroxy flavones - S. UMAMAHESWARI; K.S.SRIDEVI SANGEETHA (International Journal of Pharma and Bio Sciences, 2019)
Flavonoids are polyphenolic compounds ubiquitously present in almost all parts of flowering plants with many interesting pharmacological actions reported. Flavonoids are the rich source of antioxidant. The antioxidant nature of flavonoid may be beneficial in all inflammatory disease condition, once such condition is Arthritis. Rheumatoid arthritis is the most important cause among rheumatic disorders. In most active period of life, the people are affected by rheumatic arthritis which causes chronic inflammation of the joints. Antioxidants are the compounds helpful in preventing this oxidative damage. Hence, safe, effective and economical antioxidant and antiarthritic compounds have to be explored from the natural resources available. The aim of the present study was to investigate the antioxidant and anti-arthritic activity of selected dihydroxy flavones such as 2’,3’- dihydroxy flavone (2’, 3’-DHF) and 2’, 4’ dihydroxy flavones (2’, 4’-DHF)in vitro methods. They were synthesized and authenticated using melting point and UV spectroscopic methods. Antioxidant activity was studied using DPPH method. Anti-arthritic activity of selected dihydroxy flavones was evaluated by inhibition of protein denaturation in-vitro. 2’,3’-DHF and 2’, 4’-DHF was found to have significant antioxidant activity with IC50 values 42 µg/ml and 45 µg/ml respectively. Both the flavones showed significant anti-arthritic activity having percentage inhibition as 61.8% (2’, 3’-dihydroxy flavone), 68.6% (2’, 4´-dihydroxy flavone) when compared to that of the standard 94.3% (Diclofenac sodium). The percentage protection by 2’, 4´-dihydroxy flavone was found to be slightly high when compared to 2’, 3´-dihydroxy flavone.